Pomegranate juice is potentially better than apple juice in improving antioxidant function in elderly subjects - Guo, Changjiang; Wei, Jingyu; Yang, Jijun; Xu, Jing; Pang, Wei; Jiang, Yugang (Nutrition research (New York, N.Y.), 2008)
In the present study, 26 elderly subjects were recruited and randomly divided into 2 groups, that is, apple (low in antioxidant capacity) and pomegranate (high in antioxidant capacity) groups, and 250 mL of juice was consumed daily for 4 weeks. Changes in plasma antioxidant capacity, activity of antioxidant enzymes, contents of ascorbic acid, vitamin E, reduced glutathione, malondialdehyde, oxidized low-density lipoprotein and carbonyls, and the degree of DNA damage in mononuclear blood cells were measured. Urine samples were collected for determination of 8-hydroxy-2′-deoxyguanosine content. Increased plasma antioxidant capacity and decreased plasma carbonyl content were demonstrated after daily consumption of pomegranate juice. In comparison, apple juice consumption presented a less significant effect on antioxidant function in elderly subjects. It is concluded that daily consumption of pomegranate juices is potentially better than apple juice in improving antioxidant function in the elderly. Because the plasma ascorbic acid, vitamin E, and reduced glutathione contents did not differ significantly between the 2 groups in this study, the phenolics may be the functional components contained in pomegranate juice that accounted for the observations.